Surgical research: Exploring our history — navigating the future - Nadeem Ahmed Siddiqui; Muhammad Shahzad Shamim; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
In the fifteenth century, trained individuals called’ barber surgeons’ mastered the art of handling sharp instruments and performing basic surgical procedures. They even founded a ’United Company of Barber Surgeons’ in 1540.1 Besides shaving and haircutting, they were trained to perform dental extractions and a few surgical procedures. Later in 1745, qualified doctors and surgeons came together and founded ’Company of Surgeons’ in the UK, which later became the Royal College of Surgeons in London.2 This progression from anecdotal experiences of the guild of barbers to a formal society that helped the implementation of scientifically reasoned decisions by Royal College Surgeons was only possible because surgeons were able to appreciate the value of the evidence and incorporate it into their practices. Continuous...